Prevention of osteoporosis in postmenopausal women: a systematic review (Research, Society and Development, 2022)
Introduction: Osteoporosis is an osteometabolic disease considered silent and mainly affects the female population during the postmenopausal period of the woman. Therefore, disease prevention is the most efficient method to prevent the occurrence that fractures and becomes fundamental for postmenopausal women. Methodology: An exploratory descriptive study. The systematic bibliographic analysis was performed according to the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes). The databases used were SciELO and PubMed. Results: Data analysis found 4,967 articles. After careful reading, considering the inclusion and exclusion criteria, 5 articles were selected for the design of the present study. Discussion: There are prevention methods that consist mainly of healthy lifestyle habits in women, even though the postmenopausal organism is more susceptible to the development of osteoporosis. The practice of physical activities and adequate intake of calcium and vitamin D proved to be the most effective preventive methods. Conclusion: The lifestyle habits of postmenopausal women can act directly as favorable or preventive factors in relation to the development of osteoporosis.